Electric Vehicles in Indonesia: Public Policy, Impact, and Challenges - Ilham Pambudi; Vishnu Juwono (Asian Journal of Social and Humanities, 2023)
Indonesia's population is still growing, and the demand for energy for transport to sustain community mobility grows yearly. On the other hand, environmental challenges and green energy policies have become critical issues in today's countries, including Indonesia, and are the key subjects in sustainable development. So far, Indonesian transportation has relied on fossil-fuel vehicles. Fossil fuel vehicles negatively influence the environment due to exhaust gas emission pollution and an economic burden on the State Budget due to the substantial energy subsidies that the government must pay each year. Electric vehicles can suit people's mobility demands while remaining environmentally beneficial due to their lack of pollutants and exhaust emissions. The Indonesian government has devised different regulations to stimulate the usage of electric vehicles to support the three key programs in the National Medium-Term Development Plan For 2020-2024. This study will go through electric car policy issues, including the consequences of the policy's implementation in Indonesia. The literature review strategy is used in this study. The author thoroughly evaluated prior studies on electric vehicles in the literature. The research findings reveal that the electric car policy impacts direct and indirect expenses, but the government will have difficulty assessing the program's indirect advantages. As a result, the author suggests that the government take immediate steps to anticipate various negative impacts that may arise so that they do not become problems in the future and do not become barriers to achieving the goals of Indonesia's battery-based electric vehicle program